Beauty is in the eye of the beholder: The effect of corporate tax avoidance on the cost of bank loans - Iftekhar Hasan; Qiang Wu; Hao Zhang; Chun-Keung (Stan) Hoi (Bank of Finland, 2014)
We find that firms with greater tax avoidance incur higher spreads when obtaining bank loans. This finding is robust in a battery of sensitivity analyses and in two quasi-experimental settings including the implementation of Financial Accounting Standards Board Interpretation No. 48 and the revelation of past tax sheltering activity. Firms with greater tax avoidance also incur more stringent non-price loan terms, incur higher at-issue bond spreads, and prefer bank loans over public bonds when obtaining debt financing. Overall, these findings indicate that banks perceive tax avoidance as engendering significant risks.
URN:NBN:fi:bof-20140807160
Keywords: G21; H26; 330; Tax avoidance; Cost of bank loans; Information risk; Agency risk; Audit risk; FIN 48